Genomic Insight of Alicyclobacillus mali FL18 Isolated From an Arsenic-Rich Hot Spring - Aulitto, Martina; Gallo, Giovanni; Puopolo, Rosanna; Mormone, Angela; Limauro, Danila; Contursi, Patrizia; Piochi, Monica; Bartolucci, Simonetta; Fiorentino, Gabriella (Frontiers in Microbiology, 2021)
Extreme environments are excellent places to find microorganisms capable of tolerating temperature, pH, salinity, pressure and other toxic compounds beyond the limit for humans. In the last decades, extremophilic microorganisms have been extensively studied since they can be applied in several fields of biotechnology along with their enzymes. In this context, the characterization of heavy metal resistance determinants in thermophilic microorganisms is the starting point for the development of new bio-systems and bioprocesses for environmental monitoring and remediation. This work focuses on the isolation and the genomic exploration of a new arsenic resistant microorganism, classified as Alicyclobacillus mali FL18. The bacterium was isolated from a hot mud pool of the solfataric terrains in Pisciarelli, a well-known hydrothermally active zone of the Campi Flegrei volcano near Naples in Italy. Genomic and phenotypic analyses showed a high resistance of Alicyclobacillus mali FL18 to arsenite As(III), in agreement with the presence of different arsenic resistance genes interspersed in the genome. In addition, this bacterium was found to be resistant to other metals such as nickel, cobalt and mercury, suggesting that the solfataric environment has positively selected these resistances.